2016
DOI: 10.5604/12321966.1226859
|View full text |Cite
|
Sign up to set email alerts
|

Association of anthropometric measures of obesity and chronic kidney disease in elderly women

Abstract: Introduction and objective. Growing evidence suggests that obesity is an important contributor to the development of chronic kidney disease (CKD). The relationship between obesity and CKD is complex and not completely understood, and the best anthropometric index of obesity in predicting CKD is controversial. This study aimed to determine the best anthropometric index of obesity in predicting CKD in a population of elderly women. Materials and methods. Anthropometric indexes of obesity including body mass inde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 22 publications
(46 reference statements)
0
7
0
Order By: Relevance
“…A related study conducted among female subjects aged 65–80 years found that WHtR was a better index associated with CKD when comparing with other common adiposity indices (BMI, WC, waist-to-hip ratio) [ 23 ]. Dai et al suggested that a visceral adiposity index was superior to BMI and WC for predicting CKD in females [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…A related study conducted among female subjects aged 65–80 years found that WHtR was a better index associated with CKD when comparing with other common adiposity indices (BMI, WC, waist-to-hip ratio) [ 23 ]. Dai et al suggested that a visceral adiposity index was superior to BMI and WC for predicting CKD in females [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…15,20 Jaroszynski's study showed the existence of a relationship between incidence of CKD and obesity (p<0.001). 21 Obesity contributes to serious morbidities and leads to increased disability and mortality. Weight loss in obese patients is essential to reduce the rate of cardiovascular morbidity.…”
Section: Discussionmentioning
confidence: 99%
“…Nowadays, anthropometric researches have confidently taken its place in medicine. So they are useful not only for health assessment, but also are used in many fields: forensic medicine (to estimate the age of the subject) [13], forensic dentistry (it is an interdiscipline of forensic medicine and stomatology) for the identification of individual and age estimation [24], dentistry (anthropometric diagnostic methods of dentognathic anomaly, and there is potential correlation among number of teeth, chewing ability and anthropometric profile) [7,9,29], pediatrics, obstetrics and gynecology [17,21,27], as well as for the diagnosis of overweight (important indicators of nutritional status in the children and adults) [11,16,20], for sports control [22] and for the standardization purpose [3,15,23,26,30]. The symptoms of many diseases are expressed in anthropometric changes [12].…”
Section: Introductionmentioning
confidence: 99%